Do Czech prepositions assign case? - Veselý, Luboš (Bohemica Olomucensia, 2024)
There are two interpretations of the relationship between the preposition and the form of the noun: 1) the preposition requires a complement to which it assigns a case; 2) the preposition does not control the case and specifies its semantics. The task of the article is to try to say whether one of the concepts is more accurate.
Keywords: prepositional case; prepositional phrase; preposition; case